Validation, Employability, and Volunteering in Spain: The Case of the VOL+ Program (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
This article presents the case of the Volunteering Plus (VOL)Program for the certification of transversal competencies obtained through volunteering by the Plataforma del Voluntariado de España (PVE; Spanish Volunteering Platform). It describes in detail the process and its evaluation system, offering results from recent evaluations that show how this type of program can contribute to improve the employability profile of volunteers. This data reaffirms the value of volunteering as a learning context while demonstrating the benefits of implementing validation processes for non-formal and informal learning within the framework of the European Guidelines.